Charter and Ordinances of the City of La Crosse, with the Rules of the Common Council, at 176, Ordinance no. 14, § 15 (1888) - (:unkn) unknown (My University, 1881)
It shall be unlawful for any person other than a policeman or other officer authorized to maintain the peace and to serve process to carry or wear any pistol, slungshot, knuckles, bowie knife, dirk or any other dangerous weapon, and any person convicted of a violation of this section shall be punished by a fine not exceeding one hundred dollars. In all cases of conviction hereunder, any and all dangerous weapons found on the person accused shall be confiscated and become the property of the City of La Crosse.
Keywords: CARRY